The effects of alpha lipoic acid on muscle strength recovery after a single and a short-term chronic supplementation - a study in healthy well-trained individuals after intensive resistance and endurance training - Isenmann, E.; Trittel, L.; Diel, P. (Journal of the International Society of Sports Nutrition, 2020)
Background: Alpha lipoic acid (ALA) has been demonstrated to have anti-inflammatory activity and was tested as a drug for the treatment of various diseases. ALA is also frequently used as a nutrition supplement, in healthy individuals or in competitive athletes. However, information from intervention studies investigating physiological effects of an ALA in athletes after exercise is limited. Therefore, the aim of this study was to investigate the effects of single and short-term chronic ALA supplementation on the muscle strength recovery and performance of athletes after intensive exercise.